Genetic Diversity of Escherichia coli Coharboring mcr-1 and Extended Spectrum Beta-Lactamases from Poultry. - Jamil, Arslan; Zahoor, Muhammad Asif; Nawaz, Zeeshan; Siddique, Abu Baker; Khurshid, Mohsin (BioMed Research International, 2022)
Background. The emergence of resistance to beta-lactam agents in poultry results in multidrug-resistant (MDR) phenotypes in Escherichia coli isolates from poultry birds. The appearance of mobile colistin resistance (mcr) genes in the poultry sector has further worsened the situation. Therefore, the current study is aimed at investigating the molecular epidemiology of mcr harboring colistin-resistant E. coli among poultry. Methods. The isolation and identification of colistin-resistant E. coli (CR-Ec) were done from the broiler's fecal samples through culturing using selective media supplemented with colistin sulfate (4 μg/ml). The antibiogram studies of the isolates were performed using the disc diffusion method and broth microdilution method as per CLSI guidelines. The screening for the genes conferring resistance to colistin as well as beta-lactam agents was performed by PCR. The genetic diversity of mcr-positive strains was assessed by multilocus sequencing typing (MLST). Results. Out of 500 fecal samples, 7% (35/500) were found positive for the presence of colistin-resistant E. coli (CR-Ec). Among the CR-Ec isolates, 74.28% (26/35) were detected as ESBL producers carrying the blaCTX-M-1 gene in 15/35 (42.85%) isolates and blaCTX-M-15 and blaTEM genes in 21/35 (60%) and 35/35 (100%) isolates, respectively. E. coli isolates were found positive for the presence of mcr-1, although none of the isolates exhibited the mcr-2 or mcr-3 genes. The MLST of CR-Ec has shown the ST1035 as the most prevalent genotype, while 82.85% (29/35) of CR-Ec strains belonged to clonal complex (CC) 131 comprising ST1035, ST131, ST1215, ST1650, and ST2279. Conclusions. The findings suggest a continuous monitoring system in veterinary and clinical settings to avoid unnecessary antibiotics. Further studies are needed at the national level to help control the increasing resistance among Enterobacterales in poultry settings.